Pelatihan Pemanfaatan dan Pendampingan Pembuatan QRIS (QR Code Indonesian Standard) Sebagai Media Digitalisasi ZIS di Desa Glinggang Kabupaten Ponorogo - Mustofa Aji Prayitno; Wirawan Fadly (Universitas Lambung Mangkurat, 2022)
In the era of digitalization, the role of technology needs to be maximized to make it easier for someone to continue to do good to others, one of which is through digitization in giving donations or charity. Through digitalization, the community will be facilitated in distributing Zakat, infaq, and sadaqah whenever and wherever. The purpose of this research and community service are 1) To provide an understanding to the community about the use of QRIS (QR Code Indonesian Standard) as a ZIS (Zakat, Infaq, and Sadaqah) digitalization medium; 2) to assist in making QRIS at the Baitul Muttaqien Mosque in Glinggang Village as a digital media for ZIS; 3) Providing understanding to the community in general, and the residents of Glinggang Village in particular, that paying ZIS to help others, can still be done amid all forms of restrictions, such as during the Covid-19 pandemic. The method used in this community service research is the ABCD (Asset-Based Community Driven) method with six stages including 1) Discovery; 2) Dream; 3) Design; 4) Define; 5) Destiny; and 6) Reflection. This community service research was carried out from June to August 2021. The reflection results show that the people in Glinggang Village generally provide excellent feedback on the implementation of the community service program. Through this community service activity, the hopes and dreams of the Glinggang Village community to take an early step by digitizing various aspects of life, especially in the religious aspect, can be realized.